A experiência do ensino e aprendizagem em sala de aula - Junqueira, Ágatha Fernandes [UNESP]; Junqueira, Ana Clara Solfa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper makes references to the experience in teaching that we live through Centro de Línguas at UNESP Marília, a project of extension with which university students have the opportunity to teach other students, staff members of the university and people of the community all over the region of Marília.

Este trabalho faz referencia a experiência em ensino que vivenciamos no Centro de Línguas da UNESP Marília, um projeto de extensão em que alunos da universidade ministram aulas para outros alunos, funcionários e comunidade de toda a região.
Keywords: Lessons; Languages; Experience; Aulas; Línguas; Experiência